Effects of Bacillus Sp. on The Growth of Immature Plants In Year 1 Robusta Coffee Clones - Muhammad Ghufron Rosyady; Subakti, Bawafi; Setiyono; Erwin Kusbianto , Dwi (Journal of Soilscape and Agriculture, 2022)
Coffee (Coffea sp.) is a plantation crop that is widely cultivated and an export commodity that has an important role for the economy in Indo-nesia. The productivity of coffee cultivation in Indonesia is still not optimal due to several factors, one of which is the lack of innovative tech-nology that can increase the production of coffee plants. An important phase in the cultivation of coffee plants is in the phase of young plants or immature plants in year 1. In this phase, proper maintenance treatment is needed for the purpose of preparing the plant for optimal growth. The application of technology to increase the production of coffee plants can be done through the application of Bacillus sp. which can func-tion as bacteria that can stimulate plant growth and by using superior clones. The purpose of this study was to determine the effect of Bacillus sp. on the growth of immature plants in year 1 on several robusta coffee clones. The method of this research was using split plot design which was arranged in a randomized complete block design (RCBD) with 2 factors and 3 replications. Factor I as the main plot consisted of several clones with 4 levels, namely the Cabutan clone, BP 409, BP 936, and BP 939. Factor II as the subplot was the concentration of Bacillus sp. consisted of 3 levels, namely 0 gr/l, 30 gr/l and 60 gr/l. The results of this study indicate that there is no interaction between the application of Microbial Bacillus sp. with some of robusta coffee. While the application of Bacillus sp. significantly increase stem diameter and there were differences in the growth characteristics of several coffee clones on all observed variables.